Quantitative Evaluation of the Effectiveness of Erbium Glass Laser Therapy for Acne Scars - Wiktoria Odrzywołek; Anna Deda; Dagmara Kuca; Małgorzata Bożek; Krzysztof Makarski; Sławomir Wilczyński (Applied Sciences)
Background: Acne scarring presents a significant esthetic and psychological concern, commonly classified into atrophic and hypertrophic types. Effectively managing these lesions often involves the use of therapeutic strategies such as laser treatments, dermabrasion, and fillers. This study investigates the efficacy of 1550 nm erbium glass laser therapy in the treatment of atrophic acne scars through a quantitative assessment. Material and Methods: Participants with mild to moderate atrophic acne scars received two sessions of fractional erbium glass laser therapy at one-month intervals. Skin density and epidermal thickness were measured using a high-frequency ultrasound device (DUB SkinScanner), while the Antera 3D imaging system facilitated a comprehensive analysis of skin parameters, including texture, volumetric depressions, and pigmentation. Results: The use of this therapy led to significant improvements across multiple parameters. Skin density and epidermal thickness increased. Significant reductions were observed in fold depth, pore volume, and depression volume, indicating enhanced smoothness and minimized scar appearance. Improvements in texture roughness and pigmentation contributed to a visually coherent skin surface. Conclusions: Fractional erbium glass laser therapy effectively ameliorates the appearance of atrophic acne scars by increasing skin density, reducing dermal depressions, and improving texture and pigmentation uniformity. The Antera 3D system and high-frequency ultrasound device demonstrated high efficacy in capturing subtle changes, supporting its value in clinical applications for optimizing treatment parameters.